Phytoremediation of Fe(III) Using Pistia stratiotes L. - Efficiency and Kinetic Insights - Raisya Fadilah Putri; Fikrah Dian Indrawati Sawali; Moh Azhar Afandy (Magister Program of Material Science, Graduate School of Universitas Sriwijaya, 2026)
The increasing presence of heavy metals (dense metallic elements, such as iron, which can be toxic at high levels) in industrial wastewater poses a substantial threat to environmental and human health, requiring the development of effective, sustainable treatment solutions. This study analyzes the potential of Pistia stratiotes L. (also known as Kiambang, a floating aquatic plant) as a phytoremediation agent (an organism that removes pollutants from the environment) for extracting Iron (III) (the trivalent, oxidized form of iron) from synthetic wastewater (water with artificially added contaminants). The experiment was conducted in batch reactors (containers where reactions occur in set amounts) under controlled conditions, with modifications to the number of plants and contact length (the duration plants are exposed to contaminated water) to evaluate the effectiveness of iron removal. Iron concentrations were monitored spectrophotometrically (by measuring the amount of light absorbed by sample solutions) over time, and the phytoremediation kinetics (the rate and mechanism of pollutant removal) were investigated using zero, first, and second-order kinetic models (mathematical approaches to describe how quickly reactions occur). Results indicated that Pistia stratiotes L. was highly effective at reducing Fe (III) levels, achieving removal efficiencies exceeding 99% under optimal conditions-specifically with 10 plants and 5 days of contact time. Kinetic analysis indicated that the second-order model provided the best fit, suggesting a chemisorption-dominated process (removal primarily involves chemical bonding between the plant and iron ions). These findings emphasize the potential of Pistia stratiotes L. as a green and efficient solution for Fe (III) removal from wastewater and offer significant insight into optimizing phytoremediation system design for industrial applications.